EXPLORING ENGAGEMENT COMPONENTS IN STUDENTâ€™S UNION CASE STUDY: KMM-ITB - Priyagung, Ahmad; Ghazali, Achmad (Journal of Business and Management, 2018)
Abstract.Engagement is a desirable condition found to be useful in many types of organization both for the organization itself and for the employees. Engaged workers tend to perform better both at the level of individual and organizational. Organizations who nurture and manage engagement, have the possibility to have â€œhappierâ€ employees who performs better, which makes engagement be a possible source of competitive advantage among organizations. Nowadays, engagement is tightly linked with business-based organizations. However, any type of organization need its worker to perform better. Making organizations, who could not motivate their workers with incentive or financial rewards, find creative practices in keeping their employee engaged. Coming from a business and management student, Keluarga Mahasiswa Manajemen (KMM) of Institut Teknologi Bandung is a student union who does not puts profit as its main goal. Having to keep being organized and existed with limitations that KMM have, there are still members who voluntarily worked for KMM. Thus, KMM may have unique insights on managing engagement through its components.This study aims to explore engagement components in the case of KMM-ITB by using JD-R Model as a reference in defining the components of engagement. The purpose of this study is to provide insights of how engagement components contributes in forming engagement in the case of KMM-ITB.Result of this study shown that 4 components belong to Job Demands and 3 components belong to Job Resources (A and B). This study shows that the interaction between Job Demands and newly classified Job Resources A would result in the memberâ€™s decision to be active or not. Whereas the memberâ€™s decision to be engaged or not is more likely to happen in the exposure of Job Resources BKeywords: Engagement, JD-R Model, Non-profit Organization, Organizational Development, Studentâ€™s Union.